Bilateral sabre-like tibial deformity in secondary syphilis: case report. Issue 6 (December 1989) - Kumar, B; Gupta, R; Sharma, S C; Khandelwal, N
Abstract : A girl aged 12 years having early acquired syphilis with a rare bilateral sabre-like tibial deformity is reported.